Sex differences in visuospatial abilities persist during induced hypogonadism. (29th January 2016) - Guerrieri, Gioia M.; Wakim, Paul G.; Keenan, P.A.; Schenkel, Linda A; Berlin, Kate; Gibson, Carolyn J.; Rubinow, David R.; Schmidt, Peter J.
Abstract: Background: Despite well-established sex differences in the performance on tests of several cognitive domains (e.g., visuospatial ability), few studies in humans have evaluated if these sex differences are evident both in the presence of circulating sex hormones and during sex steroid hormonal suppression. Sex differences identified in the relative absence of circulating levels of estradiol and testosterone suggest that differences in brain structure or function exist independent of current hormonal environment and are more likely a reflection of differing developmental exposures and/or genetic substrates. Objective: To evaluate cognitive performance in healthy eugonadal men and women before and again during GnRH agonist-induced hypogonadism. Methods: Men ( n =16) and women ( n =15) without medical or psychiatric illness were matched for IQ. Cognitive tests were performed at baseline (when eugonadal) and after 6–8 weeks of GnRH agonist-induced gonadal suppression. The test batteries included measures of verbal and spatial memory, spatial ability, verbal fluency, motor speed/dexterity, and attention/concentration. Data were analyzed using repeated-measures models. Results: During both eugonadism and hypogonadism, men performed significantly better than women on several measures of visuospatial performance including mental rotation, line orientation, Money Road Map, Porteus maze, and complex figure drawing. Although some test performances showed an effect of hormone treatment, the majority of these differences reflected an improved performance during hypogonadism compared with baseline (and probably reflected practice effects). Conclusion: The well-documented male advantage in visuospatial performance, which we observed during eugonadal conditions, was maintained in the context of short-term suppression of gonadal function in both men and women. These findings suggest that, in humans, sex differences in visuospatial performance are not merely dependent on differences in the current circulating sex steroid environment. Thus sex differences in visuospatial performance in adulthood could reflect early developmental effects of sex steroid exposure or other environmental exposures differing across the sexes as our data confirm that these differences are independent of circulating estradiol or testosterone levels in men and women. Highlights: Sex differences in mental rotation were confirmed before hormone manipulation. Sex differences in visuospatial abilities were maintained during hypogonadism. Cognitive performance was not dependent on circulating sex steroids.